Monitoring the formation of a colloidal lipid gel at the nanoscale: vesicle aggregation driven by a temperature-induced mechanism. Issue 36 (20th August 2021) - Talló, Kirian; Pons, Ramon; González, César; López, Olga
Abstract : A process involving rupture and fusion of lipid vesicles leads to branched vesicular aggregates at the nanoscale, conferring gel-like behaviour. Abstract : Colloidal gels made of lipid vesicles at highly diluted conditions have been recently described. The structure and composition of this type of material could be especially relevant for studies that combine model lipid membranes with proteins, peptides, or enzymes to replicate biological conditions. Details about the nanoscale events that occur during the formation of such gels would motivate their future application. Thus, in this work we investigate the gelation mechanism, which consists of a lipid dispersion of vesicles going through a process that involves freezing and heating. The appropriate combination of techniques (transmission electron microscopy, differential scanning calorimetry and synchrotron small angle X-ray scattering) allowed in-depth analysis of the different events that give rise to the formation of the gel. Results showed how freezing damaged the lipid dispersion, causing a polydisperse suspension of membrane fragments and vesicles upon melting. Heating above the lipids' main phase transition temperature promoted the formation of elongated tubular structures. After cooling, these lipid tubes broke down into vesicles that formed branched aggregates across the aqueous phase, obtaining a material with gel characteristics. These mechanistic insights may also allow finding new ways to interact with lipid vesicles to form structured materials. Future works might complement the presented results with molecular dynamics or nuclear magnetic resonance experiments.